Transparansi Pelayanan Publik Terhadap Penyerapan Investasi Pada DPMPTSP Provinsi Sumatera Utara - Siti Alfaini Syarifah; M. Ridwan (Transformasi: Journal of Economics and Business Management, 2023)
Transparency is an important concept in line with the desire to enforce good governance practices. The government is required to be open and ensure that the public can access various information on public policy processes, budget allocation dor policy implementation, and monitor and evaluate policy implementation. The cocept of transparency point to a state in wich all aspects of the service process are open. This study aims to evaluate the impact and affectiveness of the implementation of One-Door Integrated services (PTSP) in improving public services, especially in term of investment licensing. The research method used is a quantitative approach, with analysis if case studies at the One-Door Integrated Investment and Service Office. Data were collected through interviews, observations, and analysis of related documents. The results of this study suggest in improving investment services, with of information, convenient facilities supporting investment. This study provide recommendations to identify the positive impact of the DPMPTSP’s effort in promoting investment growth through transparency in public services in creating a more conducive ivestment environment.